Shortages of Medicines to Treat COVID-19 Symptoms during the First Wave and Fourth Wave: Analysis of Notifications Reported to Registers in Austria, Italy, and Spain - Diana Ivonne Rodríguez Sánchez; Sabine Vogler (MDPI AG, 2023)
The study aimed to investigate medicine shortages of critical relevance in the pandemic. A total of 487 active substances for the treatment of COVID-19-related symptoms and therapeutically similar medicines were reviewed as to whether or not a shortage had been notified in Austria, Italy, and Spain for February 2020, March 2020, April 2020 (first wave of the pandemic), and, in comparison, in November 2021 (fourth wave). Publicly accessible shortage registers managed by the national regulatory authorities were consulted. For 48 active substances, a shortage was notified for at least one of the study months, mostly March and April 2020. Out of these 48 active substances, 30 had been explicitly recommended as COVID-19 therapy options. A total of 71% of the active substances with notified shortage concerned medicines labeled as essential by the World Health Organization. During the first wave, Spain and Italy had higher numbers of shortage notifications for the product sample, in terms of active substances as well as medicine presentations, than Austria. In November 2021, the number of shortage notifications for the studied substances reached lower levels in Austria and Spain. The study showed an increase in shortage notifications for COVID-19-relevant medicines in the first months of the pandemic.